An organic-inorganic hybrid antimony-based oxyfluoride second-order nonlinear optical crystal material and its preparation and application
By introducing π-conjugated organic moieties with hydroxy functional groups into antimony salt, organic-inorganic hybrid antimony oxygen fluoride crystal material (C5H5NO) (Sb2OF4) was constructed, which solved the problem of insufficient performance of ultraviolet NLO crystal materials in the prior art, achieved a strong frequency doubling effect and a large birefringence, and met the needs of high-performance short-wave ultraviolet NLO crystal materials.
Patent Information
- Application Number
- CN202410195333.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-22
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-02-22
AI Technical Summary
It is difficult to develop high-performance ultraviolet NLO crystal materials with excellent performance, especially in terms of SHG effect and birefringence in the ultraviolet region.
By introducing π-conjugated organic moieties with hydroxy (-OH) functional groups, combined with atomic bond engineering strategy in antimony salt, an organic-inorganic hybrid antimony oxygen fluoride crystal material (C5H5NO) (Sb2OF4) was constructed. This material realizes the regulation of intermolecular bonding in antimonate, forming crystals with excellent nonlinear optical properties.
The material exhibits strong powder frequency doubling effect (12×KDP), large birefringence (0.513@532nm) and short UV cut-off edge (270nm), meeting the needs of high-performance short-wave UV NLO crystal materials.
Smart Images

Figure CN117987918B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nonlinear optical crystal materials, and relates to an organic-inorganic hybrid antimony-based oxyfluoride second-order nonlinear optical crystal material and a preparation method and application thereof. Background Art
[0002] As a type of optoelectronic functional material, the most typical feature of second-order nonlinear optical (NLO) crystals is the frequency doubling effect (SHG), which has important application prospects in cutting-edge fields such as laser frequency conversion, laser signal holographic storage, and optoelectronic modulation. Currently, commercialized NLO crystal materials include β-BaB2O4 (BBO), LiB3O5 (LBO), KH2PO4 (KDP), and KTiOPO4 (KTP). With the development of laser technology and the emergence of tunable lasers, nonlinear optical devices have developed rapidly, and laser frequency doubling, frequency mixing, optical parametric oscillation and amplification, and photorefractive devices have appeared one after another. This has put forward more and higher performance requirements for NLO crystal materials, but the current development of NLO crystal materials is still difficult to meet these requirements. Therefore, it is urgent to develop new NLO crystal materials with excellent performance.
[0003] Oxides are a representative class of NLO crystalline materials with rich structures and excellent optical properties. In the past few decades, researchers have introduced oxygen-containing anions (such as [BO3] 3- , [PO4] 3- , [VO6] 7- , [IO3] - , [SbO n ] -2n+3 ) or fluorine-containing oxygen anions (such as [BO3F] 4- , [PO3F] 2- 、[VO n F 6-n ] -n-1 , [SbO n F m ] -2n-m+3 ) and other functional units, and developed a series of new NLO crystal materials. Due to the typical ionic bonding of metal cations, it is difficult for the functional units of traditional inorganic NLO crystals to achieve consistent arrangement and high-density stacking during the material assembly process, thus failing to achieve a large SHG effect and sufficient birefringence in the ultraviolet region. Summary of the invention
[0004] The purpose of the present invention is to provide an organic-inorganic hybrid antimony-based oxyfluoride second-order nonlinear optical crystal material and its preparation and application, so as to solve the current problems such as the lack of high-performance ultraviolet NLO crystal materials.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] One of the technical solutions of the present invention provides an organic-inorganic hybrid antimony-based oxyfluoride second-order nonlinear optical crystal material, whose chemical formula is (C5H5NO)(Sb2OF4), belongs to the monoclinic system, its space group is Cm (No.8), and the unit cell parameters are α=90°,β=99.06°~99.26°,γ=90°,Z=2,the unit cell volume is
[0007] The present invention proposes a π-conjugated organic molecule confinement strategy based on the concept of atomic bond engineering. According to the strategy, a π-conjugated organic moiety molecule with a hydroxyl (-OH) functional group is introduced into antimonate to regulate the intermolecular bonding, and an organic-inorganic hybrid antimony oxyfluoride crystal material (C5H5NO)(Sb2OF4) is successfully constructed. The crystal material exhibits a strong powder frequency doubling effect (12×KDP), a large birefringence (0.513@532nm) and a short ultraviolet cutoff edge (270nm). The present invention not only provides a new perspective for clarifying the complex relationship between motif bonding, structural polarity and NLO properties, but also provides a valuable strategy for the development of high-performance short-wave ultraviolet NLO crystal materials.
[0008] The crystal structure of (C5H5NO)(Sb2OF4) of the present invention is as follows Figure 1 As shown. The crystal structure of (C5H5NO)(Sb2OF4) consists of a one-dimensional chain They are connected to each other by intermolecular forces along the c-axis, and each one-dimensional chain is composed of polar [4-HPY(Sb2O2F4)] building blocks connected to each other by hydrogen bonds. In the [4-HPY(Sb2O2F4)] module, the cis dimer [Sb2O2F4] is combined with the neutral 4-HPY molecule through polar ionic bonds.
[0009] The second technical solution of the present invention provides a method for preparing an organic-inorganic hybrid antimony-based oxyfluoride second-order nonlinear optical crystal material, comprising the following steps:
[0010] (1) mixing an organic source, an antimony source, a fluorine source and water to form an initial mixed raw material, placing the mixed raw material in a closed hydrothermal reactor, heating and crystallizing the mixed raw material, cooling the mixed raw material to room temperature, and obtaining a clear and transparent solution;
[0011] (2) The obtained solution is evaporated at room temperature to obtain colorless transparent crystals, which are the target product.
[0012] Furthermore, the organic source is 4-hydroxypyridine.
[0013] Furthermore, the antimony source is antimony trioxide.
[0014] Furthermore, the fluorine source is hydrofluoric acid.
[0015] Furthermore, the amount of organic source, antimony source, fluorine source and water added to the initial mixed raw material satisfies: the molar ratio of organic source, antimony element, fluorine element and water is (1-10): (1-10): (1-40): (0-100), preferably (1-10): (1-10): (1-20): (0-40). When the molar amount of water is 0, it indicates that water is not added separately at this time. In addition, preferably, the molar amount of water is not 0.
[0016] Further, the temperature of the heating crystallization is 70-100° C., and the crystallization time is not less than 24 hours. More preferably, the temperature of the heating crystallization is 90-100° C., and the crystallization time is not less than 48 hours.
[0017] Furthermore, the cooling rate is 0.5 to 15°C / h. More preferably, the cooling rate is 0.5 to 5°C / h.
[0018] Further, the volatilization time at room temperature is not less than one week. More preferably, the volatilization time at room temperature is not less than two weeks.
[0019] The third technical solution of the present invention provides an application of an organic-inorganic hybrid antimony-based oxyfluoride second-order nonlinear optical crystal material in a laser frequency converter, an optical parametric oscillator, an optical parametric amplifier and a photoelectric rectifier.
[0020] Furthermore, the second-order nonlinear optical crystal material is used in laser frequency converters. Under 1064nm laser irradiation, it can output 532nm laser, and its powder frequency doubling intensity is 12 times that of KDP crystal, and can achieve phase matching. Under 1200-1900nm laser irradiation, it can output 600-950nm laser, and its powder frequency doubling intensity is 0.4-1 times that of KTP crystal.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] (1) The present application provides a new second-order nonlinear optical crystal (C5H5NO)(Sb2OF4). The crystal material has a strong frequency doubling effect. Under 1064nm laser irradiation, the frequency doubling intensity is 12 times that of KDP crystal, and phase matching can be achieved. Under 1200-1900nm laser irradiation, the frequency doubling intensity is 0.4-1 times that of KTP crystal. In addition, the crystal material has high optical transmittance in the ultraviolet visible near-infrared region, and its ultraviolet absorption cutoff edge is 270nm. The thermal decomposition temperature is 235℃. The crystal material has broad application prospects in the field of nonlinear optics.
[0023] (2) The present application also provides a method for preparing the nonlinear optical crystal (C5H5NO)(Sb2OF4), which uses a two-step method of hydrothermal and solution evaporation to prepare a colorless (C5H5NO)(Sb2OF4) crystal. The synthesis method is convenient, the synthesis conditions are mild, and it is easy to obtain a single crystal with high optical quality and high purity. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the crystal structure of (C5H5NO)(Sb2OF4);
[0025] Figure 2 The X-ray diffraction pattern of sample 1# obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is compared with the pattern obtained by X-ray diffraction test after sample 1# is ground into powder and the pattern obtained by X-ray diffraction test after being exposed to air for one month;
[0026] Figure 3 is the UV-Vis-NIR transmission spectrum of sample 1#;
[0027] Figure 4 is the infrared spectrum of sample 1#;
[0028] Figure 5 This is the thermogravimetric analysis spectrum of sample 1#;
[0029] Figure 6 It is the second harmonic signal diagram of sample 1# and standard KDP sample with the sample size ranging from 150 to 200 μm and the laser wavelength of 1064 nm;
[0030] Figure 7 This is the second harmonic phase matching diagram of sample 1# in the 1064nm band;
[0031] Figure 8 It is the second harmonic signal diagram of sample 1# and standard sample KTP with sample size in the range of 150-200μm and laser wavelength in the range of 1200-1900nm. DETAILED DESCRIPTION
[0032] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0033] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.
[0034] Embodiment 1:
[0035] Preparation of samples 1# to 6#
[0036] An organic source (i.e. 4-hydroxypyridine), an antimony source (i.e. antimony trioxide), a fluorine source (i.e. 40%wt HF) and water are mixed in a certain proportion to form a starting material, placed in a closed hydrothermal reactor, heated for crystallization, cooled to room temperature, and a clear and transparent solution is obtained; the obtained solution is slowly evaporated at room temperature to obtain colorless and transparent (C5H5NO)(Sb2OF4) crystals.
[0037] The relationship between the types and proportions of raw materials in the initial mixture, crystallization temperature, crystallization and volatilization time and sample number is shown in Table 1.
[0038] Table 1 Correspondence between samples, raw materials and synthesis conditions
[0039]
[0040]
[0041] Embodiment 2:
[0042] Crystal structure analysis of samples 1# to 6#
[0043] The structures of samples 1# to 6# were analyzed using single crystal X-ray diffraction and powder X-ray diffraction methods.
[0044] The single crystal X-ray diffraction test was carried out on a D8 VENTURE CMOS X-ray single crystal diffractometer from Bruker, Germany. The data collection temperature was 100K and the diffraction light source was graphite monochromatized Mo-Kα rays. The scanning mode was ω; the data were processed for absorption correction using the Multi-Scan method. The structure analysis was completed using the Olex2 program package; the positions of heavy atoms were determined using the direct method, and the coordinates of the remaining atoms were obtained using the difference Fourier synthesis method; the F-based 2 The full-matrix least-squares method was used to refine the coordinates of all atoms and the anisotropic thermal parameters.
[0045] The powder X-ray diffraction test was carried out on a Bruker D8 X-ray powder diffractometer from Bruker, Germany. The test conditions were a fixed target monochromatic light source Cu-Kα, a wavelength The voltage and current are 40 kV / 20 A, the slits DivSlit / RecSlit / SctSlit are 2.00 deg / 0.3 mm / 2.00 deg respectively, the scanning range is 10-70°, and the scanning step is 0.02°.
[0046] Among them, the single crystal X-ray diffraction results show that samples 1#~6# have the same chemical formula and crystal structure, the chemical formula is (C5H5NO)(Sb2OF4), belongs to the monoclinic system, the space group is Cm, and the unit cell parameters are α=90°,β=99.06°~99.26°,γ=90°,Z=2,the unit cell volume is
[0047] Take sample 1# as a typical example, its crystal structure data is α=90°,β=99.155°,γ=90°,Z=2,the unit cell volume is Its crystal structure is Figure 1 shown.
[0048] The powder X-ray diffraction test results show that in the XRD spectra of samples 1# to 6#, the positions of the sample diffraction peaks and the diffraction peaks fitted by the single crystal data are the same.
[0049] Take sample 1# as a typical example. Figure 2 As shown in the figure, the X-ray diffraction pattern obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is consistent with the pattern obtained by X-ray diffraction test after sample 1# is ground into powder. The peak position and peak intensity are consistent, indicating that the obtained sample is of high purity. After being exposed to air for one month, no obvious impurity peaks were observed in the powder X-ray diffraction pattern of sample 1# crystal compared with the previous one, indicating that the (C5H5NO)(Sb2OF4) crystal has good stability.
[0050] Embodiment 3:
[0051] UV-Vis-NIR transmission spectrum test
[0052] The UV-Vis-NIR transmission spectrum test of sample 1# was conducted on a Carry 5000 UV-Vis-NIR spectrophotometer from Agilent Technologies, USA. Figure 3 As shown by Figure 3 It can be seen that the compound has no obvious absorption from 270nm to 2000nm, which proves that the compound has a wide optical transmission range and an optical band gap of 4.59eV.
[0053] Embodiment 4:
[0054] Infrared spectrum test
[0055] The infrared spectrum test of sample 1# was conducted on a Nicolet iS10 Fourier infrared spectrometer from Thermo Fisher Scientific Inc., USA. The results are as follows Figure 4As shown, the characteristic absorption peaks in the infrared spectrum indicate the presence of 4-hydroxypyridine groups and Sb-O / F bonds in the sample.
[0056] Embodiment 5:
[0057] Thermogravimetric testing
[0058] The thermogravimetric test of sample 1# was conducted on a Netzsch STA 409PC thermogravimetric analyzer manufactured by Netzsch Equipment Manufacturing Co., Ltd., Germany. The results are shown in the figure below. Figure 5 As shown by Figure 5 It can be seen that the compound can be stabilized to 235°C and has good thermal stability.
[0059] Embodiment 6:
[0060] Frequency doubling test experiment and results
[0061] The frequency doubling test experiment of sample 1# is as follows: a Radiant Tunable Laser System (Amplitude, Horizon II Mid-band Optical Parametric Oscillator; 5Hz) is used to generate lasers with wavelengths of 1064nm and 1200-1900nm and use them as fundamental frequency light to irradiate the tested crystal powder, and an OceanOptics Maya2000 Pro spectrometer is used to detect the intensity of the second harmonic. The crystal sample and the standard samples KDP crystal and KTP crystal are ground separately, and crystals of different particle sizes are sieved out with a standard sieve, and the particle size ranges are 26-50, 50-74, 74-105, 105-150, 150-200, and 200-280μm, respectively. The change law of the frequency doubling signal with the particle size is observed to determine whether it can achieve phase matching. Under the same test conditions, the second harmonic intensity generated by the sample and the standard samples KDP and KTP is compared to obtain the relative size of the sample frequency doubling effect.
[0062] The test results show that the compound (C5H5NO)(Sb2OF4) has a large powder frequency-doubled effect. Under 1064nm wavelength laser irradiation, the frequency-doubled signal intensity is 12 times that of KDP crystal (such as Figure 6 ). The crystal material can achieve phase matching under 1064nm laser irradiation (such as Figure 7 ). Under 1200-1900nm wavelength laser irradiation, the frequency doubled signal intensity is 0.4-1 times that of KTP crystal (such as Figure 8 ).
[0063] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. An organic-inorganic hybrid antimony-based oxyfluoride second-order nonlinear optical crystal material, characterized in that: Its chemical formula is (C5H5NO)(Sb2OF4), it belongs to the monoclinic system, and its space group is Cm (No. 8), the unit cell parameters are a = 7.42~7.62Å, b = 13.11~13.31 Å, c = 4.48~4.68 Å, α = 90°, β = 99.06°~99.26°, γ = 90°, Z = 2, the unit cell volume is V = 429.17~469.17 Å 3 .
2. The method for preparing an organic-inorganic hybrid antimony-based oxyfluoride second-order nonlinear optical crystal material according to claim 1, characterized in that: The following steps are involved: (1) mixing an organic source, an antimony source, a fluorine source and water to form an initial mixed raw material, placing the mixture in a closed hydrothermal reactor, heating and crystallizing the mixture, and cooling the mixture to room temperature to obtain a clear and transparent solution; (2) volatilizing the obtained solution at room temperature to obtain colorless transparent crystals, which are the target product; The organic source is 4-hydroxypyridine; The antimony source is antimony trioxide; The fluorine source is hydrofluoric acid; The amounts of the organic source, antimony source and fluorine source added to the initial mixed raw material satisfy the following molar ratio of the organic source, antimony element and fluorine element: (1-10): (1-10): (1-40); The temperature of heating crystallization is 70~100 ℃, and the crystallization time is not less than 24 h.
3. The method for preparing an organic-inorganic hybrid antimony-based oxyfluoride second-order nonlinear optical crystal material according to claim 2, characterized in that: The cooling rate is 0.5~15 ℃ / h; The evaporation time at room temperature is not less than one week.
4. Application of the organic-inorganic hybrid antimony-based oxyfluoride second-order nonlinear optical crystal material as claimed in claim 1 in laser frequency converters, optical parametric oscillators, optical parametric amplifiers and photoelectric rectifiers.
5. The use of the organic-inorganic hybrid antimony-based oxyfluoride second-order nonlinear optical crystal material according to claim 4, characterized in that: The second-order nonlinear optical crystal material is used in laser frequency converters and outputs 532 nm lasers under 1064 nm laser irradiation and 600-950 nm lasers under 1200-1900 nm laser irradiation.
Citation Information
Patent Citations
Organic hybrid thioantimonate frequency-doubling crystal material and preparation and application thereof
CN110055592A
Rubidium molybdenum fluorine tellurite second-order nonlinear optical crystal material and preparation thereof, and application of rubidium molybdenum fluorine tellurite second-order nonlinear optical crystal material in laser frequency conversion
CN113481599A